Genetic variability, correlation, path analysis and construction of selection index in mulberry silkworm, Bombyx mori L. I. Genetic variability (University Journal of Zoology, Rajshahi University, 2012)
The genotypic variability and heritability for nine quantitative characters in 65 varieties of silkworm, B. mori L. have been investigated. Variation among genotypes were highly significant (p